A Survey on Building Systems in Malaysia - Mohamed Badir, Yuosre F. (1998)
In recent years the term "system" has been frequently used in the "Operational Research" jargon, probably is a result of the terms "Systematic Approach" and "Systematic Analysis". In some minds the term system represents computerization, but this word has been used in other fields as well, explaining the complexity and interrelationship between the parts such as building system. Because of this broadness of activities and functions that the term "system" denotes, it has recently been used in the field of construction to show the variety of complex problems which are closely related within the process of building. Malaysia is presently look at building systems as an answer to housing shortage problem. The main advantages of using building system are, speed, quality, and economics, all of which are required to meet such a large demand for housing. The clear understand of the current status of building systems will help to set the housing programs under the Seventh Malaysia Plan (1996-2000). However, the first step in any advance study on building systems and its technology should be initiated by knowing the status quo. In this thesis, three case studies and questionnaire survey were conducted. The case studies have been conducted on the unconventional construction methods, which are full prefabricated; cast in-situ; and composite construction methods. The questionnaire survey was carried out on the building system companies to understand their building system usage and current status. On the basis of the study, the building systems existing in Malaysia have been classified according to the method of construction and type of production.